What is the Role of Personalization Technology in Online Marketing, and What are its Advantages and Ethical Aspects? (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
This study discusses the adoption of personalization technology in online marketing between benefits and ethics. Personalization technology enables marketers to deliver preferable content, increase engagement, and targeting precision. Though the benefits weigh notably high, it raises a substantial number of ethical issues concerning consumer privacy, data handling as well as transparency and accountability in the process. This will be an exploratory quantitative research design with information gathered from 418 respondents aged 18 years and above who have ever experienced personalized marketing. Descriptive statistics and structural equation modeling techniques were used to measure how perceived benefits relate to ethical considerations. The findings thus confirm that personalization technology expediently brings about good customer experience conversion rates as well as targeting efficiency in marketing campaigns, however much end-users currently feel a great risk related to issues pertaining to their personal information being violated or mishandled by marketers. Such duality explicates the ambidexterity role of personalization technology both advances novelty into online marketing and generates sources of ethics. It presses the need for rules, clarity-by-design tips, and organizational blame to make sure good use and keep consumer trust. The study gives hands-on and book smarts into how personalization tech can maximize marketing smarts while tackling ethical duties in the changing scene of online marketing.